2008
DOI: 10.1158/1541-7786.mcr-08-0082
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine-1-Phosphate and Interleukin-1 Independently Regulate Plasminogen Activator Inhibitor-1 and Urokinase-Type Plasminogen Activator Receptor Expression in Glioblastoma Cells: Implications for Invasiveness

Abstract: Glioblastoma multiforme is an invasive primary brain tumor, which evades the current standard treatments. The invasion of glioblastoma cells into healthy brain tissue partly depends on the proteolytic and nonproteolytic activities of the plasminogen activator system proteins, including the urokinase-type plasminogen activator (uPA), plasminogen activator inhibitor 1 (PAI-1), and a receptor for uPA (uPAR). Here we show that sphingosine-1-phosphate (S1P) and the inflammatory mediator interleukin-1 (IL-1) increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 53 publications
(61 reference statements)
2
40
0
Order By: Relevance
“…This inhibition of migration via S1P 2 was mediated by G 12/13 -dependent Rac inactivation and Rho-dependent PTEN (phosphatase and Tensin homolog inhibitory) pathway. The stimulation of glioblastoma cells with S1P increased PAI-1 expression via S1P 2 receptor-mediated by activation of ERK1/2 and Rho pathways ( 13 ). We have confi rmed and extended these observations and now report that HDL3 and S1P stimulate the release of PAI-1 from 3T3 adipocytes via the S1P 2 receptor ( Fig.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…This inhibition of migration via S1P 2 was mediated by G 12/13 -dependent Rac inactivation and Rho-dependent PTEN (phosphatase and Tensin homolog inhibitory) pathway. The stimulation of glioblastoma cells with S1P increased PAI-1 expression via S1P 2 receptor-mediated by activation of ERK1/2 and Rho pathways ( 13 ). We have confi rmed and extended these observations and now report that HDL3 and S1P stimulate the release of PAI-1 from 3T3 adipocytes via the S1P 2 receptor ( Fig.…”
Section: Discussionsupporting
confidence: 78%
“…Results from in vitro studies have shown that insulin and isolated lipoproteins, especially tri glyceride-rich lipoproteins, stimulate PAI-1 production by cultured endothelial cells and hepatocytes ( 11,12 ). Of particular relevance to the present study, sphingosine-1-phosphate (S1P) has been shown to increase the mRNA and protein expression of PAI-1 in glioblastoma cells ( 13 ). S1P is a lysophospholipid that is emerging as key signaling molecule involved in the regulation of a variety of cellular functions, including cell growth and differentiation, proliferation, apoptotic cell death, and infl ammation (14)(15)(16)(17)(18)(19).…”
Section: Quantitative Analysesmentioning
confidence: 64%
“…S1P can induce in vitro lymphatic endothelial cell (LEC) tube formation via activation of S1PR1 ( 77,89 ). Moreover, Ang2-induced in vitro lymphangiogenesis was suppressed by a SphK1-specifi c pharmacological inhibitor ( 90,91 ), suggesting cross talk between Ang2 and S1P signaling pathways ( 37 ). Interestingly, LEC-specifi c deletion of SphK1 in the SphK2 knockout mouse, i.e., total knockout of S1P production specifi cally in LECs, inhibited lymphatic vessel maturation, indicating that SphKs and S1P in LECs are required for proper development of lymphatic vessels ( 92 ).…”
Section: Inside-out Signaling Of S1p In Tumor-induced Lymphangiogenesismentioning
confidence: 99%
“…Similarly, in glioblastoma cells, we and others have shown that S1P regulates a number of proteases that may be important for invasion and metastasis. Thus, S1P induces expression of uPA and its receptor, as well as plasminogen activator inhibitor, which leads to increased uPA activity [50,51] . Furthermore, neutralizing antibodies to uPA blocked S1P-receptor-induced invasion of glioblastoma cells in an in vitro spheroid invasion assay [51] .…”
Section: Metastasismentioning
confidence: 99%
“…Furthermore, neutralizing antibodies to uPA blocked S1P-receptor-induced invasion of glioblastoma cells in an in vitro spheroid invasion assay [51] . Upregulation of the uPA system appears to be mediated by S1P1 and S1P2 receptors [50,51] . Thus, although S1P2 is generally anti-migratory, it may contribute to invasion of glioma cells.…”
Section: Metastasismentioning
confidence: 99%